PENGARUH PEMBERIAN TENS DAN McKENZIE EXERCISE TERHADAP PENINGKATAN FUNGSIONAL LUMBAL PADA PENDERITA ISCHIALGIA AKIBAT HNP LUMBAL DI RSUD PANGKAJENE DAN KEPULAUAN - Hasnia Ahmad; Annisa Berliani Dahmadi; Sitti Muthiah (Politeknik Kesehatan Makassar, 2021)
Background: Ischialgia is pain that is felt along the sciatic nerve and continues along the leg. Ischialgia can be caused by a herniated nucleus pulposus which causes radicular pain due to disc pressure on the nerve roots exiting the intervertebral foramen. Ischialgia can cause functional lumbar barriers in carrying out daily activities, especially sitting for a long time, walking long distances and standing for a long time.Methods: This study was a pre-experimental study with a one group pretest-posttest design, aiming to determine the effect of TENS and McKenzie Exercise on improving lumbar function in patients with ischialgia due to lumbar HNP. This research was conducted at Pangkajene and Kepulauan Hospital, with the sample being ischialgia sufferers due to lumbar HNP who fit the inclusion criteria. The number of samples was 28 people who were given treatment in the form of TENS and McKenzie Exercise 12 times. Lumbar functional measurement using the Oswestry disability index.Results: Based on the descriptive test in this study, the mean lumbar functional value before treatment was 44.839 to 29.336 with a difference of 15.504 after treatment. The statistical results using the Wilcoxon test show that p = 0.000 is less than α = 0.05 (p < α) which means that the working hypothesis is accepted.Conclusion: TENS and McKenzie Exercise have a significant effect on improving lumbar function in patients with sciatica due to lumbar HNP.Keywords: Transcutaneous Electrical Nerve Stimulation, McKenzie Exercise, Lumbar Functional, Lumbar HNP